EMERGENCY CONDITIONS IN SURGERY - Milojkovic, Bobana D (Acta medica Medianae, 2020)
Acute intestinal obstruction is a complex pathological condition in 90% of the cases caused by colorectal cancer (CRC). Unfortunately, despite the advances in diagnostic, in 20% of patients with this cancer, the diagnosis is made on the operating table during the emergency surgery for acute obstruction of the colon. Mortality in emergency operations is 15-20%, while the morbidity is in 40-50% of the cases. The aim of this study was to determine the incidence of acute intestinal obstruction caused by CRC, the localization of obstruction and types of applied surgical procedures. A prospective clinical study was conducted at the Department of General Surgery KC-Nis and included patients treated for acute intestinal obstruction caused by colorectal cancer, in the period from 2011. to 2014. Because of the acute intestinal obstruction caused by CRC, a total of 129 patients underwent surgery. The median age of treated patients was 60.2 years, the youngest patient was 42 and the oldest 80. The largest number of patients was in T3 stage. Obstructive cancer was localized on the right colon in 34 patients (26.35%), on the left colon in 53 (41.08 %) patients and in the rectum in 42 patients (32.55%). Total colectomy was performed in 2 (1.55%) patients, subtotal colectomy in 4 (3.1%) patients, a right hemicolectomy was performed in 16 patients (12.40%), left hemicolectomy in 6 patients (4.65% ), Hartmann’s procedure was performed in 29 (22.48%) patients, ileo- transverso anastomosis in 11 (8.52%) patients, ileo-sigmoid anastomosis in 4 (3.10) patients, Miles procedure in 3 (2.32%) patients , ileostomy in 2 patients (1.55%), colostomy in 47 (36.43%) patients and resection of the sigmoid colon in 5 (3.87%) patients. Out of 129 patients operated for acute intestinal obstruction due to CRC, 25 patients died, representing a mortality rate of 19.37 %, and morbidity rate was 35.65%. The final decision to render on the type of surgical procedure is made on the basis of the surgical findings, the general condition of the patients and the experience of the surgeon. Each of these surgical procedures in the treatment of CRC has its advantages, disadvantages and indication areas. Key words: Acute intestinal obstruction, colorectal cancer, surgical treatment